From an Interesting Patient to a Publishable Paper - Frank Mosler; Gerd Nöldge; Keivan Daneshvar (Swiss Journal of Radiology and Nuclear Medicine, 2026)
Radiological case reports are most useful when they enable readers to reconstruct the clinical question, inspect the decisive original imaging evidence, follow the diagnostic reasoning, and evaluate how the diagnosis was confirmed and what happened afterwards. CARE-radiology provides the radiology-specific reporting framework. This Educational Editorial & Practical Guide translates CARE-radiology, CARE, ICMJE, COPE, the 2024 Declaration of Helsinki and CRediT into a 12-step SJORANM workflow for authors, reviewers and editors. SJORANM requires original diagnostic radiological images as primary evidence and a dedicated Patient Perspective section (or a transparent explanation if unobtainable). Pathology is preferred when clinically relevant and available but is not mandatory when another credible reference standard exists. The framework distinguishes external reporting requirements, good scientific practice and journal-specific policy. Accompanying tools include author and reviewer checklists, a technical pre-check, standardised decision-letter modules and a CARE-radiology crosswalk. The aim is an educational, internally consistent and independently verifiable case report before peer review.